3D numerical investigation of the coupled interaction behavior between mechanized twin tunnels and groundwater – A case study: Shiraz metro line 2. (September 2020) - Shivaei, Sina; Hataf, Nader; Pirastehfar, Keivan
Highlights: Modified Cam-Clay model better portrays the behavior of the lean clay of Shiraz region. The more permeable the grout layer, the wider the settlement trough width. The drainage condition of the grout layer greatly affects the internal lining forces. The position of the groundwater level greatly affects the twin-tunnel interaction mechanism. The rest period is the key factor in the long-term interaction behavior between twin tunnels. Abstract: Mechanized tunneling method using Tunnel Boring Machine (TBM) is being extensively employed in urban areas, especially when excavation takes place underneath the groundwater table. In this study, three-dimensional coupled Finite Element Analyses (FEA) have been performed to investigate the interaction mechanism between mechanized twin tunnels construction of Shiraz metro (line 2) and groundwater. Firstly, two soil constitutive models (Mohr-Coulomb and Modified Cam-Clay model) of Shiraz lean clay are validated against drained triaxial compression test data. Varying the permeability of the grout layer within the specified range, the base numerical model is then calibrated by the field data of ground surface settlements. Parametric studies are conducted subsequently to evaluate the effects of influencing factors involved in the coupled FEA of twin tunnels, including the drainage boundary condition of the grout layer, the position of groundwater level, and the rest interval between excavations of twin tunnels. The numerical results indicate that the ground surface settlements and internal forces of existing segmental lining are greatly influenced by the drainage condition of the grout layer. Also highlighted is the marked effect of the drainage condition of the grout layer in the numerical prediction of the interaction behavior between mechanized twin tunnels and groundwater in different cases of the groundwater level and the rest interval between excavations of twin tunnels.